TRACING RELIGIOUS TRANSFORMATIONS IN URBAN SOCIETY DURING THE KUTARINGIN KINGDOM ERA - Anwar, Khairil; Hartati, Zainap; Ahmad, Sabarudin; Husain, Muhammad Zidni (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Institut Agama Islam Negeri Metro, 2024)
This research article aims to explore the traces of religious transformation in the urban society during the Kutaringin Kingdom era. The current population of Kutaringin, now located within the West Kotawaringin Regency, is predominantly Muslim. The Islamic influence is palpable in both the daily lives of the people and the Islamic symbols present during the current governance. This study adopts an empirical (field research), utilizing both historical and religious approach. The findings indicate that the process of religious transformation occurred peacefully without any acts of violence. Some individuals who were previously adherents of Kaharingan converted to Islam and integrated into the urban society of the Kutaringin Kingdom. Meanwhile, those who remained steadfast in their beliefs chose to reside in the hinterlands. However, their relationship with the kingdom remained strong, and the kingdom sought their opinions and approval, represented by the leaders of their communities, in addressing issues. The role of religious leaders, especially Kyai Gede, played a significant part in this transformation. Kyai Gede, whose passing is commemorated annually, played a crucial role in shaping the religious landscape. Presently, the kingdom's territory is divided into several regencies, including West Kotawaringin regency, Lamandau regency, and Sukamara regency, with the majority of the population adhering to Islam.